Island endurance - Yu, Bill (Survive! (Graphic Planet (Firm)), 2020)
Two disparate girls find themselves trapped together when a storm strands them at a resort in the Florida Keys. Includes true survival stories, a survival guide, critical thinking question, trivia, and a glossary.